An Ion‐Imprinting Derived Strategy to Synthesize Single‐Atom Iron Electrocatalysts for Oxygen Reduction. Issue 16 (11th December 2020) - Ding, Shichao; Lyu, Zhaoyuan; Zhong, Hong; Liu, Dong; Sarnello, Erik; Fang, Lingzhe; Xu, Mingjie; Engelhard, Mark H.; Tian, Hangyu; Li, Tao; Pan, Xiaoqing; Beckman, Scott P.; et al.
Abstract: Carbon‐based single‐atom catalysts (CSACs) have recently received extensive attention in catalysis research. However, the preparation process of CSACs involves a high‐temperature treatment, during which metal atoms are mobile and aggregated into nanoparticles, detrimental to the catalytic performance. Herein, an ion‐imprinting derived strategy is proposed to synthesize CSACs, in which isolated metal–nitrogen–carbon (Me–N4 –C x ) moiety covalently binds oxygen atoms in Si‐based molecular sieve frameworks. Such a feature makes Me–N4 –C x moiety well protected/confined during the heat treatment, resulting in the final material enriched with single‐atom metal active sites. As a proof of concept, a single‐atom Fe–N–C catalyst is synthesized by using this ion‐imprinting derived strategy. Experimental results and theoretical calculations demonstrate high concentration of single FeN4 active sites distributed in this catalyst, resulting in an outstanding oxygen reduction reaction (ORR) performance with a half‐wave potential of 0.908 V in alkaline media. Abstract : An ion‐imprinting derived strategy is proposed to synthesize single‐atom metal catalysts at the molecular scale. The well‐defined and isolated Fe–N4 –C x moiety is confined in SiO x matrix and then directly converted into single‐atom FeN4 active sites during the high‐temperature pyrolysis process. The final catalyst shows a high concentration of active sites and outstanding catalytic performance for oxygen reduction.